Pricing companies: Ethno-accounting of private equity activity - Marlène Benquet (Finance and Society, 2019)
How do private equity firms decide on a fair price for a business? Drawing on 76 semi- structured interviews, this article contributes to the sociology of finance and valuation studies by showing that pricing companies is not just a valuation operation but also a capital- repartition issue. In so doing, it shows how concrete, local pricing methods contribute to the financialisation of the economy through the creation of a new capital accumulation centre. The article's ethno-accounting approach describes three pricing steps: first, the capital access rules applicable to the private equity firm members (the price rationale); second, the expectations about the capital that can be transferred from the business to the private equity firm (the theoretical price level); and third, the transaction participant coordination mechanisms (culminating in the actual price). This description of the practices and concepts inherent in business valuation sidesteps the traditional divide between price formation in constructivist concepts of value as well as price discovery in substantivist concepts of value. Instead, value is defined as the expectation of a transfer of capital from the productive sphere to the private equity firm.
Keywords: 300; Private equity; ethno-accounting; accumulation centre; pricing companies; financial evaluation